2021
DOI: 10.1111/cen.14402
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical discriminants between functional hypothalamic amenorrhoea (FHA) and polycystic ovary syndrome (PCOS)

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 154 publications
(288 reference statements)
2
49
1
5
Order By: Relevance
“…Subsequent studies have confirmed the observation of elevated kisspeptin levels seen in PCOS. In a literature review by Tang et al [ 35 ] conducted in July 2018, twelve studies were found which considered serum kisspeptin levels in PCOS. Eight of the twelve studies found significantly higher serum levels in patients with PCOS.…”
Section: Kisspeptin and Pcosmentioning
confidence: 99%
“…Subsequent studies have confirmed the observation of elevated kisspeptin levels seen in PCOS. In a literature review by Tang et al [ 35 ] conducted in July 2018, twelve studies were found which considered serum kisspeptin levels in PCOS. Eight of the twelve studies found significantly higher serum levels in patients with PCOS.…”
Section: Kisspeptin and Pcosmentioning
confidence: 99%
“…( 5 ), the exclusion of other reasons for oligo-/amenorrhea is warranted in the definition criteria for both PCOS and FHA and there is no available test that is ultimately discriminating. Moreover, it has been mentioned that these diagnostic uncertainties also make the initial assignment to PCOS or FHA in studies more difficult ( 6 ). Thus, a precise definition of PCOS and FHA would be desirable in studies about this specific topic.…”
Section: Introductionmentioning
confidence: 99%
“…LH is measured routinely in clinical practice using an automated chemiluminescent immunoassay method and is the gold standard surrogate marker of GnRH. Furthermore, LH can be measured at frequent intervals (eg 10minutely) to assess GnRH/LH pulsatility, and accurate assessment of LH pulsatility could help facilitate diagnosis and treatment of patients presenting with reproductive endocrine disorders 9 . However, this is rarely done in clinical practice because it is resource-intensive, inconvenient for patients, and there is a lack of user-friendly methods for computational analysis of the LH data available to clinicians.…”
Section: Introductionmentioning
confidence: 99%